STUDI DINAMIKA SENYAWA FOSFAT DALAM KUALITAS AIR SUNGAI CILIWUNG HULU KOTA BOGOR - RTM Sutamihardja; Mia Azizah; Yunita Hardini (JURNAL SAINS NATURAL, 2018)
Study of Dynamics of Phosphate in the Water Quality in Bogor of Upstream Ciliwung RiverCiliwung River has existed and become an important part of the community since ancient period. Since 2009, the Ciliwung River has been polluted condition from upstream. One of the pollutant that could decrease the quality of river water was phosphate. Excessive phosphate level in water bodies caused nutrient enrichment conditions (eutrophication). The presence of nitrate supporting phosphate also caused algae blooming, one of the environmental problem. The research was conducted to determine the dynamics of the phosphate compound of Ciliwung River whether the pollution was reduced, same, or worse. The research included sampling of river water at three points of Katulampa, Pasar Bogor, and Warung Jambu River with sampling time interval of 8 hours in a day for 3 weeks in a row. The data of phosphate and nitrate concentration were measured and compared to the results in PP No.82 year 2001. The total of phosphate in Ciliwung river water has exceeded threshold level in accordance with the environmental quality standard of PP. 82 year 2001, and has been indicated to be in eutrophication condition.Keywords: Ciliwung River, Water Quality, Water Pollution, Phosphate.ABSTRAKSungai Ciliwung telah ada dan menjadi bagian penting masyarakat sejak zaman purba. Namun seiring dengan berlalunya waktu dan perkembangan pesat, sejak tahun 2009 Sungai Ciliwung telah tercemar dari hulu. Salah satu polutan yang bisa menurunkan kualitas air sungai adalah fosfat. Keberadaan fosfat yang berlebihan di badan air dapat menyebabkan kondisi pengayaan nutrisi (eutrofikasi), dan dengan dukungan nitrat dapat menyebabkan algae blooming yang menjadi salah satu masalah lingkungan. Penelitian ini dilakukan untuk mengetahui dinamika senyawa fosfat Sungai Ciliwung apakah pencemarannya berkurang, sama, atau lebih buruk. Ruang lingkup penelitian meliputi pengambilan sampel air sungai pada tiga titik Katulampa, Pasar Bogor, dan Warung Jambu dengan interval waktu sampling 8 jam dalam sehari, dan dilakukan setiap minggu selama 3 minggu berturut-turut. Kemudian dilakukan analisis sampel di laboratorium, serta interpretasi data dengan membandingkan hasilnya terhadap PP No.82 tahun 2001. Nilai total fosfat di air sungai Ciliwung Hulu tidak memenuhi standar kualitas lingkungan PP. 82 tahun 2001, dan diindikasikan berada dalam kondisi eutrofikasi.Kata kunci: Sungai Ciliwung, Kualitas Air, Polusi Air, Fosfat.